2019
DOI: 10.1371/journal.pone.0225933
|View full text |Cite
|
Sign up to set email alerts
|

Host-mediated microbiome engineering (HMME) of drought tolerance in the wheat rhizosphere

Abstract: Host-mediated microbiome engineering (HMME) is a strategy that utilizes the host phenotype to indirectly select microbiomes though cyclic differentiation and propagation. In this experiment, the host phenotype of delayed onset of seedling water deficit stress symptoms was used to infer beneficial microbiome-host interactions over multiple generations. By utilizing a host-centric selection approach, microbiota are selected at a community level, therein using artificial selection to alter microbiomes through bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 30 publications
3
86
0
Order By: Relevance
“…Although this new theory is mainly related to biotic stresses, Liu et al (2015) showed that the respiratory metabolic capacity of mycorrhizal rice (Oryza sativa) under low-temperature stress accelerated the biosynthesis of strigolactone to recruit AMF (Glomus intraradices). On the other hand, in a study published by Jochum et al (2019b), it was possible to modify the phenotype of Triticum aestivum subsp. aestivum, using host-mediated microbiome engineering as a strategy to improve the resistance of this crop to drought stress.…”
Section: Natural Microbiome Engineering the New Horizons To Alleviatmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this new theory is mainly related to biotic stresses, Liu et al (2015) showed that the respiratory metabolic capacity of mycorrhizal rice (Oryza sativa) under low-temperature stress accelerated the biosynthesis of strigolactone to recruit AMF (Glomus intraradices). On the other hand, in a study published by Jochum et al (2019b), it was possible to modify the phenotype of Triticum aestivum subsp. aestivum, using host-mediated microbiome engineering as a strategy to improve the resistance of this crop to drought stress.…”
Section: Natural Microbiome Engineering the New Horizons To Alleviatmentioning
confidence: 99%
“…In this context, microbiome engineering has recently emerged as an alternative to promote positive interactions between microorganisms and host plants (Mueller and Sachs, 2015;Sheth et al, 2016;Foo et al, 2017;Timmusk et al, 2017;Trivedi et al, 2017;Hussain, 2019). Recently, Jochum et al (2019b) have performed host-mediated microbiome engineering to attribute drought resistance in wheat plants, which demonstrates the potential for modification of native microbiomes to attribute crop resistance. Thus, the transfer of whole microbiomes to improve crop yields under different stress situations could represent an unparalleled advance to start a new revolution in the bioinoculants development (Santoyo et al, 2017;Woo and Pepe, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These challenges of engineering community functions have motivated a surge of interest in evolution-inspired approaches, which treat the community as a unit of selection and explore its ecological landscape in search of consortia with desirable traits (Swenson et al 2000b;Arias-Sánchez et al 2019). This approach has been found to work in silico (Xie et al 2019;Williams 2007;Williams and Lenton 2007;Penn 2003;Doulcier et al 2020) and it has been attempted several times in the laboratory to optimize functions such as toxin removal (Swenson et al 2000a), the manipulation of environmental pH (Swenson et al 2000b), or the modulation of various host traits (Panke-Buisse et al 2015Swenson et al 2000b;Mueller et al 2016;Mueller and Sachs 2015;Gopal and Gupta 2016;Jochum et al 2019). The results of these experimental studies have been mixed (Blouin et al 2015;Arora et al 2019), and it is becoming increasingly clear that the details of how exactly the "offspring" communities are generated from the "parental" communities can be critical for the success of this approach (Raynaud et al 2019;Mueller et al 2016).…”
mentioning
confidence: 99%
“…The difficulty of engineering community functions from the bottom-up (Escalante et al 2015) has motivated a surge of interest in evolutionary design (Bentley 1999) approaches, which treat the community as a unit of selection and explore the ecological landscape in search of consortia with desirable traits (Arias-Sánchez et al 2019) . This approach has been found to work in silico (Penn 2003,Williams andLenton 2007a,b;Doulcier et al 2019;Xie et al 2019) and it has been attempted several times in the laboratory to optimize functions such as toxin removal (Swenson et al 2000a) , the manipulation of environmental pH (Swenson et al 2000b) , or the modulation of various host traits (Swenson et al 2000b;Mueller and Sachs 2015;Panke-Buisse et al 2015Gopal and Gupta 2016;Mueller et al 2016;Jochum et al 2019) . The results of these experimental studies have been mixed (Blouin et al 2015;Arora et al 2019) , and it is becoming increasingly clear that the details of how exactly the "offspring" communities are generated from the "parental" communities can be critical for the success of this approach (Mueller et al 2016;Raynaud et al 2019) .…”
Section: Introductionmentioning
confidence: 99%